An Analysis of Slang Language Used In English Students’ Interaction - Nehru Pasoloran Pongsapan (Universitas Cokroaminoto Palopo, 2022)
The slang is one of the language variations recently used mostly in the English students’ daily interaction. The students use this language variation in various types and reasons. This paper reports the results of a qualitative study which is aimed at finding and exploring the types of the slang language and the reasons of using slang in students interaction. It is used as the method to describe the result of a process based on the category that has been determined. The data are collected from document analyses and close-ended questionnaires and are analyzed by using the interactive model of data analysis: data reduction, data display, and drawing conclusion/verification. The study finds that the types of the slang language used in the students’ interaction show various results in each type. The first highest result is the acronym (33 words or 39.75%). The second is clipping 23 words or 27.71%). The third is fresh and creative coining (16 words or 18.39%). The fourth is compounding (eight words or 9.19%). The lowest is imitation (five words or 5.74%). In relation to the reasons for the language slang use, seven reasons are found. The first reason is to enrich the language by inventing new words (Freq=15; 17.85%). The second reason is to induce friendliness (Freq=14; 16.70%). The third and fourth reasons are to be different and easing social intercourse (Freq=13; 15.47%). The fifth reason is to reduce seriousness of conversation (Freq=11; 13.09%. The sixth reason is to have fun (Freq=10; 11.90%. The last reason is to have delights in virtuosity (Freq=eight; 9.52%).